THERMOMECHANICAL MODELING OF TURNING PROCESS USING AN ARBITRARY LAGRANGIANEULERIAN (ALE) METHOD - HAIRUDIN, WAN MASRURAH (2017)
During turning processes, steels often behave in a complicated manner involving severe plastic deformation, fracture, phase change and grain size change. It is a complex process since there are several mechanisms work and interact simultaneously. As the heat generated in the cutting process raises the work piece material temperature above its critical phase transformation temperature, a metallurgical transformation will occur, and the heat and plasticity due to the transformation will affect the turning process. Mechanical deformation, heat transfer, and microstructure are all strongly coupled and affected altogether, these effects has been known thermo-mechanical coupling. There are several thermo-mechanical variables such as stress, strain, and temperature that are not easily measurable through the experimental test. These variables are induced the surface integrity of the work piece material. In this research, two different 2D models; rectangle and circular are developed with Arbitrary Lagrangian Eulerian (ALE) adaptive meshing. The commercial finite element ABAQUS 6.8 is used for modelling of AISI 1045 steel material by using carbide cutting tools. In finite element model, the tool is assumed as analytical rigid and work piece is deformable body. The cutting speed was set as 100m/min, depth of cut of 3mm and feed rate of 0.15mm/rev. The Johnson cook law material model is employed to simulate the flow stress of the work piece material. The effect of three different rake angle (α = -10°, 0° and 10°), tool edge radius (r = 0.5mm, 1.0mm and 2.0mm) and friction coefficient (μ = 0.1 and 0.4) on von Mises stress, equivalent plastic stain and temperature distribution were investigated. Based on the results, the small rake angle of -10° tends to increase the von Mises stress, equivalent plastic strain and temperature compared the larger rake angle; 0° and 10°. The larger tool edge radius (2.0mm) influences the increasing of von mises stress, equivalent plastic strain, and temperature distribution due to the close of the tool tip and high plastic deformation on the work piece.